Constructed wetlands for treatment of harvest effluents from grow-out ponds of the Amazon river prawn - Oliveira Santos, Alexandre Augusto [UNESP]; Camargo, Antonio Fernando Monteiro [UNESP] (Hindawi, 2015)
Effluent discharges from aquaculture can reduce water quality in receiving water bodies and that strategies or practices to reduce this are necessary. One possibility is to reduce, or eliminate, water renewal in grow-out ponds. In this study, we eliminated water renewal in grow-out ponds associated with the culture of 40 individualsm-2 of Amazon river prawn (Macrobrachium amazonicum). At the end of the culture period it was, however, necessary to drain the pond to harvest the prawns. An experiment was performed in triplicate, in which the water supply characteristics and harvest water characteristics of ponds were evaluated. To reduce these concentrations of total N and P, an aquatic macrophyte (Eichhornia crassipes, water hyacinth) treatment system (CWs) was adopted. The water characteristics in the CWs were evaluated after 1, 3, 7, 14 and 21days. The water supply of ponds presented the average concentrations of 0.67±0.32mgL-1 and 17.4±14.7μgL-1 of total-N and total-P respectively. The harvest effluent of ponds had elevated concentrations of different forms of nitrogen (4.44mgL-1 of total-N) and phosphorous (100.9μgL-1 of total-P). After 1day of the experiment we found the following reductions in key nutrients in treatment system containing E. crassipes: 90%, 78% and 45% reductions in the concentrations of particulate matter, orthophosphates and nitrates respectively. We noted that after 3days the nitrates had been reduced by 53%. We concluded that 3days of this treatment was sufficient for the removal of the additional nutrients that had accumulated in the Amazon river prawn ponds.
Keywords: CWs; Eichhornia crassipes; Macrobrachium amazonicum; Macrophytes; Removal efficiency; Water hyacinth